2020
DOI: 10.1097/sla.0000000000003943
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Effect of Maternal Sildenafil and Fetal Tracheal Occlusion Improves Lung Development in the Rabbit Model of Congenital Diaphragmatic Hernia

Abstract: Objective: To evaluate the effect of combining antenatal sildenafil with fetal tracheal occlusion (TO) in fetal rabbits with surgically induced congenital diaphragmatic hernia (CDH). Background: Although antenatal sildenafil administration rescues vascular abnormalities in lungs of fetal rabbits with CDH, it only partially improves airway morphometry. We hypothesized that we could additionally stimulate lung growth by combining this medical treatment with fetal TO. Methods: CDH was created on gestational day (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Another study which concluded that there was no difference in amniotic fluid levels of surfactant also did not measure SP-B 25 . In a surgical rabbit model of CDH, SP-B gene expression was reduced compared to the sham controls, as was the SP-B staining intensity determined by immunohistochemistry 26 . Boucherat et al compared surfactant levels in fetuses with CDH with unaffected fetuses at different time points during pregnancy and observed that affected lungs were significantly smaller and histologically immature, but no delay in surfactant development or content (including SP-B) in CDH fetal lungs was observed by western blotting 27 .…”
Section: Discussionmentioning
confidence: 93%
“…Another study which concluded that there was no difference in amniotic fluid levels of surfactant also did not measure SP-B 25 . In a surgical rabbit model of CDH, SP-B gene expression was reduced compared to the sham controls, as was the SP-B staining intensity determined by immunohistochemistry 26 . Boucherat et al compared surfactant levels in fetuses with CDH with unaffected fetuses at different time points during pregnancy and observed that affected lungs were significantly smaller and histologically immature, but no delay in surfactant development or content (including SP-B) in CDH fetal lungs was observed by western blotting 27 .…”
Section: Discussionmentioning
confidence: 93%
“…Many rat studies as well as a rabbit study demonstrated attenuated vascular remodelling, reduced arteriolar muscularisation and increased vessel density in hernia pups exposed to prenatal sildenafil. In rabbits, the effects of sildenafil and tracheal occlusion were synergistic 56. In addition, in fetal lambs with CDH, maternal administration also improved neonatal pulmonary haemodynamics and gas exchange 57.…”
Section: Methodsmentioning
confidence: 96%
“…In a surgical rabbit model with CDH, sildenafil reduced the proportional wall thickness of peripheral lung vessels to the normal range, increased vascular branching, improved airway morphometry, and postnatal lung mechanics [ 111 ]. Combined with tracheal occlusion, sildenafil’s beneficial effect on airway development and lung function was augmented in pups with CDH [ 112 ]. Similarly to the findings in the rat studies, sildenafil reduced pulmonary vascular branching in non-hypoplastic littermates [ 111 ].…”
Section: Congenital Diaphragmatic Herniamentioning
confidence: 99%